Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1528-1167.2008.01724.x
|View full text |Cite
|
Sign up to set email alerts
|

EEG‐fMRI study of the ictal and interictal epileptic activity in patients with eyelid myoclonia with absences

Abstract: SUMMARYPurpose: To investigate the blood oxygenation level-dependent (BOLD) signal changes correlated with ictal and interictal epileptic discharges using electroencephalography-correlated functional magnetic resonance imaging (EEG-fMRI) in patients with eyelid myoclonia with absences (EMA) and then to explore the pathophysiological mechanisms of epileptic discharges and their effect on brain function. Methods: Four patients with EMA were investigated through the method of EEG-fMRI. The characteristics of BOLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…3 and 4) and one with frontal encephalomalacia) had EM seizures. This supports the idea of a system epilepsy that includes pathways from the occipital to the frontal cortex with discharges spreading by thalamo-cortical networks [10] as seen by the EEG-fMRI study in patients with EMA that have shown activation in the frontal regions and the thalamus [39].…”
Section: Discussionmentioning
confidence: 69%
“…3 and 4) and one with frontal encephalomalacia) had EM seizures. This supports the idea of a system epilepsy that includes pathways from the occipital to the frontal cortex with discharges spreading by thalamo-cortical networks [10] as seen by the EEG-fMRI study in patients with EMA that have shown activation in the frontal regions and the thalamus [39].…”
Section: Discussionmentioning
confidence: 69%
“…Activation of various brain regions during cognitive tasks has also been tested with fMRI in IGE patients . Our literature search yielded 16 fMRI studies in IGE . Despite study heterogeneity, common trends emerge from EEG‐fMRI results.…”
Section: Resultsmentioning
confidence: 99%
“…Only for the left thalamic seed, decreased connectivity in the cerebellum in the area of the nodule and right dentate nucleus was detected. Several studies pointed to an cerebellar involvement in IGE patients: previous EEG‐fMRI studies on GSWDs reported BOLD signal changes in the cerebellum (Gotman et al., 2005; Liu et al., 2008), a single photon emission computed tomography (SPECT) study showed reduced interictal blood flow in the cerebellum (Joo et al., 2008), and a positron emission tomography (PET) study detected an increased binding of 11 C Flumazenil binding in cerebellar nuclei in IGE patients (Savic et al., 1994). Furthermore, cerebellar ictal hyperperfusion has been described for patients with partial seizures (Bohnen et al., 1998), and stimulation of the cerebellar dentate nucleus suppressed interictal discharges and reduced the frequency of seizures in patients with intractable epilepsy (Chkhenkeli et al., 2004).…”
Section: Discussionmentioning
confidence: 99%